Pemertahanan Bahasa Flores NTT oleh Masyarakat Desa Modo 1 Kabupaten Buol - Liputo, Istiqamah I.; Ntelu, Asna; Masie, Sitti Rachmi (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2024)
The problems studied in this research are: (a) how is the Flores NTT language used by the People of Modo 1 village in Buol Regency? (b) What are the strategies for preserving the Flores NTT language for the people of Modo 1 village in Buol Regency? (c) what factors influence the maintenance of the Flores NTT language by the people of Modo 1 village in Buol Regency? This research aims to describe the use of the Flores NTT language by the people of Modo 1 village in Buol Regency in the domains of family, social, parties, organizations, bureaucracy, and school, to describe the factors influencing language preservation and the strategies for preserving the Flores NTT language by the people of Modo 1 village in Buol Regency. The theories used were Speaking (Hymes), factors influencing language maintenance (Downes), and strategies for language maintenance (Pateda).This research was conducted in Modo 1 village, BuolRegency. The method used was a descriptive qualitative method. The data were the Flores NTT language used by the people of Modo 1 village in Buol Regency. The data collection techniques included elicitation, participant observation, and structured and unstructured interviews. The data analysis techniques involved transcribing, translating, sorting, analyzing the data, concluding, and writing the research report.The research results revealed that the use of the Flores NTT language by the people of Modo 1 village in Buol Regency is predominantly in the domains of family and social interactions, whereas in the domains of parties, organizations, bureaucracy, and school, Indonesian is predominantly used. The factors influencing the preservation of the Flores NTT language by the people of Modo 1 village in Buol Regency included: family factors, social interaction factors, communication intensity factors, activity factors, education factors, and desire or aspiration factors. The strategies for preserving the Flores NTT language by the people of Modo 1 village in Buol Regency included: parents familiarizing and teaching the Flores NTT language to their children, the community using the Flores NTT language in daily communication, traditional leaders using the Flores NTT language in various traditional activities, the government supporting cultural activities that use regional languages, and integrating lessons related to regional languages into the local content curriculum in schools. Thus, it can be concluded that the Preservation of the Flores NTT Language by the People of Modo 1 Village in Buol Regency is still sustained despite being dominated by the Indonesian language.